Penatalaksanaan Fisioterapi Pada Kasus De Quervain Syndrome Di RSUD Moewardi Surakarta - Puteri Pamungkas, Kejora; , Totok Budi Santoso, S.Fis, MPH (2015)
Background: De quervain syndrome is a disease to inflammation of the tendon from m. abductor pollicis longus and m. extensor policis brevis together into one tendon sheath. Characterized by swelling and difficult in activity associated with the thumb. Aims of research: To study about physiotherapy management in reducing pain, increasing range of motion and increase muscle strength in the case of De Quervain syndrome using modalities Transcutaneus Electrical Nerve Stimulation (TENS), Infra Red (IR) and Therapeutic Exercise (TL). Results: After therapy for about six times the obtained results of the assesment of tenderness T1 :2 to T6: 1 motion pain T1: 4 a T6: 3 increase range of motion active S: T1: 300-00-300, a T6: 350-00-350, increase of motion pasif S: T1: 350-00-300, a T6: 450-00-350, increase muscle strength of m. abductor pollicis brevis T1: 3 a T6: 4, dan extensor pollicis longus : T1: 3 a T6: 4. Conclusion: Transcutaneus Electrical Nerve Stimulation (TENS) can reduce pain in knee dextra in caused by De'quervain syndrome dextra. Therapeutic Exercise like active exercise, strecing, strengthening can improve range of motion in his thumb dextra in the case of de'quervain syndrome. Therapeutic exercise like active exercise, hold relax streching can improve range of motion can improve muscle strentgh in the case de'quervain syndrome